Neurorehabilitation for Adults with Brain and Spine Tumors - Hunter, Hanna; Qin, Evelyn; Wallingford, Allison; Hyon, April; Patel, Amar (Seminars in Neurology, 2023)
Central nervous system (CNS) malignancies (i.e. brain and spine tumors) and their treatments can result in a multitude of neurologic deficits. Patients with CNS malignancies experience physical, cognitive, and psychosocial sequelae that can impact their mobility and quality of life. Neurorehabilitation can play a critical role in maintaining independence, preventing disability, and optimizing safety with activities of daily living. This review provides an overview of the neurorehabilitation approaches for patients with CNS malignancies, neurologic impairments frequently treated, and rehabilitation interventions in various health care settings. In addition, we will highlight rehabilitative outcomes between patients with nononcologic neurologic conditions compared to brain and spine tumors. Finally, we address medical challenges that may impact rehabilitation care in these medically complex cancer patients.
Keywords: CNS malignancies; brain tumors; spine tumors; cancer rehabilitation; neurorehabilitation